The Correlation between Working Period and Exercise Routines with Musculoskeletal Complaints on Batik Craftsmen - Nala Astari Pramesti; Shintia Yunita Arini (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Asosiasi untuk Demokrasi dan Kesejahteraan Sosial (Ademos) was founded as a form of anxiety towards rural communities whose majority of the population does not receive enough attention and access to economic development. One of the empowerment programs is a program to improve the quality of the Bojonegoro batik craftsmen. Workers can work more than 8 hours a day in a sitting and bending position for long periods of time. This study aimed to determine the correlation between the length of work and exercise routines on musculoskeletal complaints among batik craftsmen of Ademos, Bojonegoro Regency. Methods: This research was a descriptive analytic study using a cross-sectional design. The research was conducted in July-August 2020 on Ademos batik craftsmen in Bojonegoro Regency. The total population of the study was 42 batik craftsmen who were selected using a total sampling technique. The variables studied included tenure, exercise routines, and musculoskeletal complaints. Data collection was carried out through questionnaire sheets, observations and the Nordic Body Map Questionnaire. Results: The results of the study found that there was a significant correlation between working period and musculoskeletal complaints (p=0.032) experienced by Batik craftsmen of Ademos Bojonegoro. On the other hand, there was no correlation found between exercise routines and musculoskeletal complaints (p=0.361) on Batik craftsmen of Ademos Bojonegoro. Conclusion: The significant factor causing musculoskeletal complaints in Ademos Bojonegoro Batik craftsmen was the working period factor.